Volumetric analysis of oropharynx according to craniofacial morphology using cone-beam tomography - Huamaní Guzman, Héctor Miguel (2020)
Objective. To analyze the cone-beam computed tomography (CBCT) scans of subjects with different facial biotype and different skeletal patterns to compare the volume of the oropharyngeal airway. Methods. The study was descriptive and cross-sectional. The sample consisted of 55 cone-beam scans belonging to subjects aged 15 to 43 years. The cone beam scans were grouped according to facial biotype, skeletal pattern, sex, and age groups (15 - 20, 21 - 29, and 30 - 43 years old). Cephalograms were created from the tomography to find the Vert index and the ANB angle. Data were analyzed using statistical tests: U of Mann-Whitney, ANOVA, and Kruskal-Wallis. Results. No statistically significant difference was found between oropharyngeal volume and facial biotype, nor between oropharyngeal volume and skeletal pattern. The lowest volumes were identified in subjects with class II skeletal pattern (= 8.70 ± 3.60 cm3), and in subjects with brachyfacial biotype (= 8.87 ± 2.96 cm3). There was no significant difference between volume and sex (p> 0.05). The 15-20-year-old group presented the highest volume of oropharyngeal (=11.16 ± 5.64 cm3). Also, a negative correlation was recorded between oropharyngeal volume and the ANB angle (r= -0.31, p= 0.02). Conclusions. Oropharyngeal volume according to facial biotype and the skeletal pattern does not present a significant variation for the analyzed sample. Also, the oropharyngeal volume does not vary according to sex, and the volume is greater between 15 and 20 years.